Business Plan - Boriya Bistar - Agarwal, Ashwin (2016)
The document contains a business plan for a start up business Boriya Bistar. The company is an e-commerce website based out of Bangalore, India. The business plan has discussions on the idea, finding of the market analysis, financials for the company and the risks it may possess.